2022
DOI: 10.1609/aaai.v36i11.21565
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way for Novices: How to Teach AI for K-12 Education in China

Abstract: In response to the trend that artificial intelligence (AI) is becoming the main driver for social and economic development, enhancing the readiness of learners in AI is significant and important. The state council and the ministry of education of China put AI education for K-12 schools on a high priority in order to foster local AI talents and reduce educational disparities. However, the AI knowledge and technical skills are still limited for not only students but also the school teachers. Furthermore, many lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, Tedre et al (2021) suggested that integrating AI into K-12 computing education required "abandoning the belief that rule-based 'traditional' programming is a central aspect and building block in developing next generation computational thinking." Song et al (2022) found that an AI curriculum for K-12 schools in China increased computational thinking in students, providing evidence to support connections between AI and computational thinking.…”
Section: Related Work: Ai Edu and Curriculum Designmentioning
confidence: 87%
See 1 more Smart Citation
“…However, Tedre et al (2021) suggested that integrating AI into K-12 computing education required "abandoning the belief that rule-based 'traditional' programming is a central aspect and building block in developing next generation computational thinking." Song et al (2022) found that an AI curriculum for K-12 schools in China increased computational thinking in students, providing evidence to support connections between AI and computational thinking.…”
Section: Related Work: Ai Edu and Curriculum Designmentioning
confidence: 87%
“…Reviews of prior AI curricula (Druga, Otero, and Ko 2022) and ML education research (Sanusi et al 2023) identifed that while some AI curriculum focused specifcally on AI ethics and sociotechnical systems (Krakowski et al 2022;Alvarez et al 2022), most did not engage with the social and ethical implications of AI and ML. White researchers typically do not engage teachers in the AI curriculum codesign process (Song et al 2023), interviews with 12 high school teachers in Africa identifed that teachers felt their involvement in the curriculum co-design process of resources could support contextually situating the curriculum (Sanusi, Oyelere, and Omidiora 2022).…”
Section: Related Work: Ai Edu and Curriculum Designmentioning
confidence: 99%
“…The idea is to teach young children AI by means of hands-on activities concerning knowledge-based systems, supervised machine learning and generative music. Similarly, Song et al (2022) outlines a course for elementary schools, inspired to the five big ideas of AI4K12 (Touretzky et al 2019), where block-based programming represents the backbone of several teaching modules. Also the approach described in (Akram et al 2022) uses block-based programming for explaining AI techniques and algorithms, but such a proposal adopts a multi-disciplinary perspective and AI techniques are contextualized in concrete problems.…”
Section: Related Workmentioning
confidence: 99%
“…Some examples are the Digital Education Action Plan (European Commission 2021-2027), Informatics for All (Informatics for All 2023), the National Artificial Intelligence Initiative in US (United States Government 2023), and the National Plan for a Digital School in Italy (MIM). Other proposals can be found in (Van Mechelen et al 2023;Yang 2022;Song et al 2022;Touretzky et al 2019). These initiatives are frequently supported by public funds, through which schools can buy technologies, such as tablets or educational robots, and adapt classes to become laboratories (MIM).…”
Section: Introductionmentioning
confidence: 99%
“…A few states (e.g., Georgia and Florida) are working to incorporate AI learning outcomes in their K12 curricula 1 . All states and all nations must tackle the same change in K12 education (Song et al 2023). It is essential for K12 education to adequately prepare students to be citizens in an AI-driven society, whether through in-school instruction or through educational programming in informal settings (Ali et al 2021;Lao 2020).…”
Section: Introductionmentioning
confidence: 99%